‘Am I good at this?’ Connecting ESL learners’ interest and perceived competence in grammar learning. - Zakaria, Noor Asma Iffah (Faculty of Education Universitas Negeri Malang, 2024)
The accumulation of evidence suggests that the role of interest to serve as a crucial building block for both initial motivation and ongoing engagement. The psychological state that one is in while engaging in an activity or content (such as mathematics, music, or language), as well as the motivation to continue engaging in the activity or content, are both referred to as interest. Hence, interest describes the ways in which individuals partake and indulge with activities or content. In this study, we validated Hidi and Renninger’s (2006) interest development scale (IDS) in the context of grammar learning among ELLs, which depicts “interest” as a multidimensional concept. We then consider the relation of interest to perceived competence as informed by the expectancy-value theory. Having established a model of interest and perceived competence, we tested the associations with the learners’ performance of the course. Finally, our studies' findings reaffirm the centrality of interest as a motivating factor, stimulator for engagement, and influence how they perceive themselves in relation to their learning performance.